NIKAH SUMBANG: PERSPEKTIF MORAL MASYARAKAT DI KERINCI - Gusmer, Puja Rahmanu; Syawir, Irwan; Candra, Alif Aditya (Academy of Education Journal, 2023)
This study aims to determine customary law (nikah sumbang) in a moral perspective in Kerinci Regency. In 2019-2022, there were 21 perpetrators of violations of customary law of discordant marriage committed by the community. This research is a qualitative descriptive research. Data collection techniques in this study are through observation, interviews, and documentation. With data analysis techniques in the form of data reduction, data presentation, and conclusions. The results showed that the implementation of this discordant marriage was no different from marriage in general, it's just that for this discordant marriage there was an admonition made by the upstream of the balang sent by Ninik Mamak to the person who performed the discordant marriage. Then there are sanctions from customary law applied to people who perform discordant marriages. The fine is also intended so that people who have performed discordant marriages do not become a byword for the community. The customary law of discordant marriage in a moral perspective can be said not to affect morals, one of the intentions and objectives of discordant marriage is to strengthen the tribe or strengthen the family that has long been far away so that after the marriage becomes close again.